1994
DOI: 10.1007/bf01901306
|View full text |Cite
|
Sign up to set email alerts
|

Preconceptions of students about the natural urban environment in a small Spanish city

Abstract: The preconceptions of secondary students from a small Spanish city, mainly about natural aspects, have been studied. The main characteristic of their conceptions about the urban natural environment was that it was always linked to negative aspects and was generally seen as something essentially problematic. Moreover, it seems that their knowledge of smaller living beings, of wild animals, plants and fungi, was worse than for other urban living beings. The analysis of these altemative conceptions has led the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The Environmental Protection Agency (2004) (EPA) defines environment as the built environment as well as the natural environment and all natural resources including air, land, and water. Studies that have explored students' conceptions of urban environments found that students were not able to conceptualize living organisms inhabiting built-up areas (Membiela, Nogueiras, & Suarez, 1994) and they did not consider urban areas to have wildlife (Simmons, 1994). Rickinson (2001) concluded from his review of the literature that children perceive nature as a natural and non-human entity; that is, nature is viewed as a place for recreation, leisure, and solitude, as well as a place that is threatening and dangerous to people.…”
Section: Student's Conceptualizations Of the Environmentmentioning
confidence: 99%
“…The Environmental Protection Agency (2004) (EPA) defines environment as the built environment as well as the natural environment and all natural resources including air, land, and water. Studies that have explored students' conceptions of urban environments found that students were not able to conceptualize living organisms inhabiting built-up areas (Membiela, Nogueiras, & Suarez, 1994) and they did not consider urban areas to have wildlife (Simmons, 1994). Rickinson (2001) concluded from his review of the literature that children perceive nature as a natural and non-human entity; that is, nature is viewed as a place for recreation, leisure, and solitude, as well as a place that is threatening and dangerous to people.…”
Section: Student's Conceptualizations Of the Environmentmentioning
confidence: 99%